Catalytic Enantioselective Conjugate Additions of (pin)B‐Substituted Allylcopper Compounds Generated in situ from Butadiene or Isoprene. Issue 34 (20th July 2016) - Li, Xiben; Meng, Fanke; Torker, Sebastian; Shi, Ying; Hoveyda, Amir H.
Abstract: Multicomponent catalytic enantioselective transformations that entail the combination of butadiene or isoprene (common feedstock), an enoate (prepared in one step) and B2 (pin)2 (commercially available) are presented. These processes constitute an uncommon instance of conjugate addition of an allyl moiety and afford the desired products in up to 83 % yield and 98:2 enantiomeric ratio. Based on DFT calculations stereochemical models and rationale for the observed profiles in selectivity are provided. Abstract : Catalysis with feedstock : Abundantly available butadiene and isoprene together with commercially available B2 (pin)2 participate in enantioselective multicomponent conjugate addition to enoates. Transformations are catalyzed by a copper complex of an easily accessible NHC (N‐heterocyclic carbene) ligand, affording products in up to 83 % yield, 80:20 Z : E and 98:2 e.r.